2014
DOI: 10.1017/s1368980014002547
|View full text |Cite
|
Sign up to set email alerts
|

Relative validation of fruit and vegetable intake and fat intake among overweight and obese African-American women

Abstract: Objective: To compare commonly used dietary screeners for fat intake and fruit and vegetable intake with 24 h dietary recalls among low-income, overweight and obese African-American women. Design: Three telephone interviews were completed; measures included two 24 h dietary recalls (a weekday and weekend day) using the Nutrition Data System for Research software, the Behavioral Risk Factor Surveillance System's (BRFSS) Fruit and Vegetable Consumption Module and the National Cancer Institute's (NCI) Percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
(63 reference statements)
0
17
0
Order By: Relevance
“…Second, the 24-hour dietary recall was self-reported. However, the Nutrition Data System for Research is a validated tool for collection of dietary information [ 35 ], and a technician specially trained to use the system collected the dietary data. A multiple-pass method was utilized to enhance food intake recall [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the 24-hour dietary recall was self-reported. However, the Nutrition Data System for Research is a validated tool for collection of dietary information [ 35 ], and a technician specially trained to use the system collected the dietary data. A multiple-pass method was utilized to enhance food intake recall [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, an FFQ is biased by poor participant recall of dietary intake and by participant’s provision of socially desirable responses [ 66 ]. Further, underreporting of food intake has been observed in obese individuals as well as African American women [ 70 , 71 , 72 ]. Our sample size may have limited our ability to effectively examine diet patterns for subgroups (e.g., men vs. women).…”
Section: Discussionmentioning
confidence: 99%
“…Through a further search using the International Register of Validated Short Dietary Assessment Instruments[ 11 ], 16 other short (<20 items) questionnaires that were not included in the review of Kim and Holowaty (2003) were identified. A variation in correlations coefficients was found, showing moderate [ 8 , 12 14 ] to good validity [ 5 , 8 , 15 18 ] of the questionnaires. However, none of these instruments or the instruments reviewed by Kim and Holowaty (2003) were computerised or online questionnaires.…”
Section: Introductionmentioning
confidence: 99%